Meso-Scale Shear Physics in Earthquake and Landslide Mechanics 2009
DOI: 10.1201/b10826-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermo- and hydro-mechanical processes along faults during rapid slip

Abstract: Field observations of maturely slipped faults show a generally broad zone of damage by cracking and granulation. Nevertheless, large shear deformation, and therefore heat generation, in individual earthquakes takes place with extreme localization to a zone <1-5 mm wide within a finely granulated fault core. Relevant fault weakening processes during large crustal events are therefore likely to be thermal. Further, given the porosity of the damage zones, it seems reasonable to assume groundwater presence. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
(74 reference statements)
2
13
0
Order By: Relevance
“…Although the strength at each point on the fault at low slip rates is high ( e f 0 ~ 100 MPa), averaged shear stress on a fault is low because of low coseismic shear stress and frequent rupture nucleation, consistent with the results of [4], [5], [6]. Long-term shear stress distribution and averaged shear stress in the seismogenic region (-50 km < x < 50 km) is shown in Figures 2a and b, respectively, for cases with L = 10 mm.…”
Section: Earthquake Sequences In 2d Crustal Plane Modelssupporting
confidence: 77%
See 1 more Smart Citation
“…Although the strength at each point on the fault at low slip rates is high ( e f 0 ~ 100 MPa), averaged shear stress on a fault is low because of low coseismic shear stress and frequent rupture nucleation, consistent with the results of [4], [5], [6]. Long-term shear stress distribution and averaged shear stress in the seismogenic region (-50 km < x < 50 km) is shown in Figures 2a and b, respectively, for cases with L = 10 mm.…”
Section: Earthquake Sequences In 2d Crustal Plane Modelssupporting
confidence: 77%
“…These observations suggest that most fault points have low shear stress before large earthquakes, slip mainly at even lower shear stresses, and lock with the final stress only modestly lower than the initial value. [4], [5], and [6] demonstrated that even if a fault is strong at low slip rates, a dynamic rupture can propagate on a low-stressed fault (shear stress / normal stress ~ 0.3 or less) if the strength of a fault dramatically decreases coseismically, and discussed the operation of a fault at a low long-term shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [Perrin et al, 1995;Zheng and Rice, 1998;Lapusta and Rice, 2003;Noda et al, 2009;Rice et al, 2009] also focused on propagation of ruptures at low shear prestress compared to the static strength of rocks in the laboratory. Such low shear prestress can be inferred for natural faults, for example, from the measurements of the principal stress directions at boreholes around the San Andreas fault [Hickman and Zoback, 2004;Townend and Zoback, 2004].…”
Section: Heterogeneity In the Interseismic Shear Stressmentioning
confidence: 99%
“…However, recent experiments employing near‐seismic slip velocities reveal dramatic frictional weakening in these materials, demonstrating the operation of dynamic weakening mechanisms, including flash heating of asperities, thermal pressurization of pore fluids, phase decomposition, frictional melting, and gel weakening [e.g., Rice et al , 2009; Tullis et al , 2007; Goldsby and Tullis , 2002; Di Toro et al , 2004, 2006; Hirose and Shimamoto , 2005, Han et al , 2007, 2010; Mizoguchi et al , 2007]. Dynamic fault weakening may resolve the apparent inconsistencies between estimates of static stress change and in situ crustal stress measurements [e.g., Noda et al , 2009; Rice et al , 2009]. …”
Section: Introductionmentioning
confidence: 99%